Response of Several Shallot (Allium cepa var. ascalonicum) Varieties to Alternaria porri - M. Ibrahim Danuwikarsa; Bagus K. Udiarto; Dick Dick Maulana; Asri Suaidah (Agrotechnology Research Journal, 2023)
Shallots are a valuable commodity in Indonesian civilization. However, due to different obstacles, production remains low. The prevalence of purple blotch disease caused by Alternaria porri is one of the major challenges in shallot production. A fungus infects its host through the stomata. The use of resistant cultivars is one of the initiatives to combat purple blotch disease. This study aimed to determine the resistance of several shallot varieties to purple blotch disease, identify and obtain resistant shallot varieties, and determine the relationship between stomatal density and the average intensity of the purple blotch disease attack. This study uses shallot cultivars released by the Balai Penelitian Tanaman Sayuran (BALITSA) Lembang. This study employed a randomized completely block design (RCBD) with ten shallot varieties as the treatments with three replications. The Agrihorti-1 and Katumi varieties had the lowest attack intensity, while the Sembrani and Maja Cipanas varieties had the highest assault intensity. Bima Brebes, Trisula, Mentes, Violetta-1, Kramat-1, Agrihorti-1, Agrihorti-2, and Katumi varieties were resistant to purple blotch disease, however, Sembrani and Maja Cipanas were susceptible. A low or weakly positive association exists between stomata density and the mean intensity of purple blotch illness.